THE USE OF COLLABORATIVE WRITING TECHNIQUE IN IMPROVING STUDENTS’ WRITING ACHIEVEMENT - Dewi Sartika (Universitas Islam Ogan Komering Ilir Kayuagung, 2016)
Writing as the productive skill is needed to be master by the students so as to communicate and share the information in the written form. However, students still do not aware of the importance of writing skill. As a result, students face some problems in writing, such as have a lot mistakes in students’ writing due to the limitation of the time, lack of idea and vocabulary, and less concentration. Therefore, the objective of this study was to find whether collaborative writing technique was effective or not to improve students’ writing achievement. Quasi experimental method and nonrandomized pre-test post-test control group design were used. Study population was used as the samples and flip of cubic was used to determine the experimental and control groups. As a result, morning class was selected as the experimental group and afternoon class was selected as the control group. Content validity was used to check the validity of the test and tried out of the test was applied to find out the reliability of the test. Written test was used in which the students wrote one out of the topics provided. Then, the raters judged the students’ writing based on the rubric containing the four components, namely organization, grammar, spelling, and vocabulary. To analyze the data, t-test was used. The results showed that the mean difference between post-test in the experimental and control groups was 19.166, tobtained was 5.545 at the significant level of p